The Effect of Cognitive Stimulation on Dementia Levels in the Elderly in the X Subdistrict of Jakarta - Ricky riyanto iksan; Lilis Yuliarsih; Esther Lenny Dorlan Marisi; Koko Wahyu Tarnoto; Salamah Thomasita Batu Bara; Putri Permata Sari (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
Dementia is a health problem that often occurs in the elderly and has an impact on decreased cognitive function, independence, and quality of life. Non-pharmacological efforts such as cognitive stimulation are believed to help slow the progression of dementia. Therefore, it is important to examine the effect of cognitive stimulation on the level of dementia in the elderly in the community. Objective: This study aims to determine the effect of cognitive stimulation on the level of dementia in the elderly in the X Village area of Jakarta. Method: This study used a quasi-experimental design with a pretest-posttest approach without a control group. The study sample consisted of 50 elderly people selected using a purposive sampling technique according to the inclusion criteria. The intervention in the form of cognitive stimulation was carried out for 4 weeks with a frequency of 3 times per week. The instrument used was the Mini Mental State Examination (MMSE) questionnaire. Data analysis was carried out using a paired t-test statistical test. Results: The analysis results showed an increase in MMSE scores after the Cognitive Stimulation intervention. The average score increased from 18.2 (SD 3.1) to 22.5 (SD 2.8), with a difference of 4.3 points, which is considered clinically significant. Statistical tests showed a p value of 0.000 (<0.05), which means there was a significant difference between before and after the intervention. In addition, the decrease in the standard deviation value indicates that the results after the intervention are more homogeneous. Thus, Cognitive Stimulation has been proven effective in improving cognitive function in the elderly.y. Conclusion: Cognitive stimulation significantly improves cognitive function and reduces dementia rates in the elderly. This intervention can be recommended as a promotive and preventive measure in geriatric nursing services in the community.